2020
DOI: 10.33633/jais.v4i2.2749
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Of Heart Disease Using K-Nearest Neighbor Method Based On Forward Selection

Abstract: Heart is one of the essential organs that assume a significant part in the human body. However, heart can also cause diseases that affect the death. World Health Organization (WHO) data from 2012 showed that all deaths from cardiovascular disease (vascular) 7.4 million (42.3%) were caused by heart disease. Increased cases of heart disease require a step as an early prevention and prevention efforts by making early diagnosis of heart disease. In this research will be done early diagnosis of heart disease by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…In addition, [22] observed that the ordinary version classifier in the heart disease diagnosis dataset proved that the level of accuracy had increased after being optimized with the application of the forward selection method from 73.44% to 78.66%. Then, [23] observed that the ordinary version classifier in the Movie Review Polarity V2.0 dataset [36], it was proven that the AUC level had increased after being optimized with the application of the forward selection method from 71.26% to 76.2 %.…”
Section: Literature Review Of Optimization Effortsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, [22] observed that the ordinary version classifier in the heart disease diagnosis dataset proved that the level of accuracy had increased after being optimized with the application of the forward selection method from 73.44% to 78.66%. Then, [23] observed that the ordinary version classifier in the Movie Review Polarity V2.0 dataset [36], it was proven that the AUC level had increased after being optimized with the application of the forward selection method from 71.26% to 76.2 %.…”
Section: Literature Review Of Optimization Effortsmentioning
confidence: 99%
“…Feature selection is a technique to determine the most relevant attribute in the dataset by selecting the correct subset of the original attributes because not all attributes may be relevant to the problem; even some of these attributes can interfere with the impact at reduced accuracy. In the forward selection method (FS), modeling starts with zero variables (empty model) then the variables are entered one by one until specific criteria are met [21], [22].…”
Section: Forward Selection (Fs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be overcome by minimizing dimensions or irrelevant features, one of which is feature selection. Feature selection can improve machine learning model performance and reduce computation time [21], [22]. In addition, forward selection (FS) is utilized to perform feature selection and results in improved classification performance [22]- [25].…”
Section: Introductionmentioning
confidence: 99%
“…Coffee is one product from current plantation this needed by people around the world. In Indonesia, coffee plantations have very important role for economy national, then Becomes facilitator field work for Public around [1] In Indonesia, especially in Malang Regency, people around many have coffee plantations including namely Robusta coffee and Arabica coffee local. Robusta coffee is type of coffee produced more many compared with arabica coffee.…”
Section: Introductionmentioning
confidence: 99%